SCIENCESNAP® - Wong, C.Y.; Chandran, V.G.R.; Ng, B.K.; Fung, H.H. (University of Malaya, 2015)
An online portal to be developed based on integration and analysis of scientometric data consolidated from several sources and databases globally. Using the portal the business will offer database and customized reports to those users who wish to access to science, technology and innovation indicators. This trademark registered in class 9, 16 and 42